STRUKTUR DAN FUNGSI SOSIAL KEPERCAYAAN RAKYAT UNGKAPAN LARANGAN MENGENAI PERTANIAN DAN BERCOCOK TANAM DI KANAGARIAN LAGAN HILIR PUNGGASAN KECAMATAN LINGGO SARI BAGANTI - Sari, Emelia Fermita; WS, Hasanuddin; Nst., Bakhtaruddin (Jurnal Bahasa dan Sastra, 2018)
This article aims to describe: (1) the structure of people's belief of agriculture expression and prohibition of farming in Kanagarian Lagan Hilir Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan : (2) to describe the social function of people's trust expression prohibition in Kanagarian Lagan Hilir Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan. This research type was qualitative research with descriptive method. Informant in this research was determined by purposive sampling technique, that is by determining informant first. The background of this research was in Kanagarian Lagan Hilir Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan. The instrument of this research was the researchers themselves recorders. The research data was collected through two stages, namely the recording of the oral tradition of the people's belief in the prohibition expression and the environmental stages of storytelling, the data validation using triangulation technique. Data were analyzed through the following steps: (1) data inventory stage, (2) stage of coverage, (3) data analysis, (4) stages of data analysis and discussion phase, (5) stage of reporting. The result and findings of agriculture expression and prohibition of farming in Kanagarian Lagan.Keywords: structure, social function, expression of prohibition